2015
DOI: 10.1088/0964-1726/24/11/115026
|View full text |Cite
|
Sign up to set email alerts
|

Detection of flow separation and stagnation points using artificial hair sensors

Abstract: Recent interest in fly-by-feel approaches for aircraft control has motivated the development of novel sensors for use in aerial systems. Artificial hair sensors are one type of device that promise to fill a unique niche in the sensory suite for aerial systems. In this work, we investigate the capability of an artificial hair sensor based on structural glass fibers to directly identify flow stagnation and separation points on a cylindrical domain in a steady flow. The glass fibers are functionalized with a radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The mapping function between the sensor deformation and the pressure field at the leading edge is, therefore, obtained through calibration that depends on the structure of the hair-like sensor and the flow conditions. These assumptions are supported by the investigations in references (Dickinson 2010, Dickinson et al 2012, Phillips et al 2015.…”
Section: High-fidelity Electromechanical Modelsupporting
confidence: 59%
See 2 more Smart Citations
“…The mapping function between the sensor deformation and the pressure field at the leading edge is, therefore, obtained through calibration that depends on the structure of the hair-like sensor and the flow conditions. These assumptions are supported by the investigations in references (Dickinson 2010, Dickinson et al 2012, Phillips et al 2015.…”
Section: High-fidelity Electromechanical Modelsupporting
confidence: 59%
“…In our investigation, a single hair sensor at the leading edge is considered, but the methodology could easily be extended to patches of them, as shown by Dickinson (2010), Dickinson et al (2012) and Phillips et al (2015). In fact, the same model could be used when considering the average signal from a patch of hairsensors.…”
Section: Wing Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…From the previous studies, 25 it has been found that the AHS measurements around the stagnation point might not be as good as the rest of the surface. A specific deign of AHS works well in a range of velocities, in which the sensor is sensitive to the flow.…”
Section: Flow Sensing Around Arbitrary Airfoilsmentioning
confidence: 94%
“…Alternatively, artificial hair sensors (AHS) have also been fabricated by MEMS‐free processes from high stiffness structural glass microfibers and carbon nanotubes (CNTs) . The CNTs in these devices form self‐aligned, radial arrays during synthesis that have been shown to exhibit elastic, foam‐like behavior and large piezoresistance in response to compressive strain against a conductive surface .…”
Section: Introductionmentioning
confidence: 99%